Parental denial of children with Special Educational Needs (SEN)in preschool setting: A case study - Che Ahmad, Aznan; Omar, Salizawati; Naidu, Sivabala; Gill, Ranjit Singh (Jurnal Pendidikan Bitara UPSI, 2025)
Parental denial of children with special educational needs (SEN) in preschool settings poses significant challenges to early intervention and inclusive education. While parental acceptance can facilitate timely support, many caregivers struggle with denial, often influenced by social stigma, fear of judgment, and skepticism toward professional assessments. This qualitative case study examines parental reluctance through semi-structured interviews conducted with three mothers from a preschool in North Malaysia. The interview data were analyzed using thematic analysis to identify patterns in parental responses and perceptions. The findings reveal two overarching themes: denial and social stigma. The respondents justified their child's behaviors by comparing them to family members, rejecting educators' concerns, and resisting formal diagnoses due to fear of labeling. Skepticism toward teacher assessments and personal doubts about SEN indicators further contributed to their hesitation. Moreover, social stigma played a critical role, as external pressures from extended family and community perceptions discouraged them from seeking professional evaluations. This avoidance of intervention delays critical support, potentially impacting a child's developmental trajectory. The findings underscore the importance of equipping early childhood educators with the skills to engage sensitively with parents, recognize signs of denial, and foster trust in professional assessments. Addressing these barriers requires psychoeducational programs, parent support initiatives, and public awareness campaigns to foster informed decision-making. Strengthening collaboration among parents, educators, and healthcare providers is crucial to bridging the acceptance gap. By promoting a more supportive and well-informed environment, families can be empowered to navigate their child's needs confidently. Ultimately, this study contributes to early childhood education by highlighting the need for culturally responsive engagement strategies and systemic support structures that enable timely identification and intervention for children with SEN, thereby enhancing their educational experiences and long-term well-being.